Adherence to Standard Operating Procedure for patients with Acute Cervical Spine Dislocated Injuries: A case of a teaching central referral hospital in South Africa - Ayik, Goud (Division of General Surgery, 2023)
1.1.1 Aims: To analyse the impact that the adoption of our institutional standard operating procedure (SOP) for cervical spine dislocations had on the timing of closed reduction at our hospital. 1.1.2 Patients and methods: The study was a retrospective review of patients who presented to our institution with cervical dislocation injuries and were managed with closed reduction. The patient records of acute cervical spine dislocations from 2015 to 2018, Data from the Acute Spinal Cord Injury database along with patient's demographic information were gathered and compared. Participants within the study time frame were diagnosed with a cervical facet dislocation based on clinical examination findings and radiological confirmation. Patients who had reduction performed at other referring hospitals were excluded from the study. 1.1.3 Results: The practice within all tertiary hospitals in the Western Cape is to perform closed reduction of cervical fracture dislocations as soon as possible after injury. In this study the time between injury and closed reduction before introducing the SOP was13 h 13 min and after introducing the SOP, the time increased to an average of 14 h 28 min. The main cause of delay was the transfer time from the site of injury to emergency ward. Other reasons for the delay include missed diagnosis, orthopaedic registrar unavailability, and incomplete reduction bed. 1.1.4 Conclusion: This study found that the time taken for orthopaedic management of cervical dislocations increased by an hour after introduction of the SOP. Additionally, the overall time to reduction also increased This was due to delays in transfer to the emergency ward and referral to Orthopaedics. We recommend that in our setting, reduction could be initiated within an hour of patient arrival, if emergency ward doctors rapidly identified the problem and commenced cervical traction when the orthopaedic team was not immediately available. Our impression was that there was poor adherence to the new SOP guidelines on time management by the trauma team, and possibly transport delays prior to hospital admission. A further study to investigate the bottlenecks of the referral system is advisable.